Gli incantesimi nella poesia popolare finlandese e le sue testualizzazioni - Capkova Viola; Parente Antonio (Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università di Napoli L’Orientale, 2022)
The Kalevala and The Kanteletar are respectively the epic and lyrical collection of poems compiled and heavily edited by the folk poetry collector and philologist Elias Lönnrot (1802-1884). In this paper we present a more authentic form, the original texts of Finnish folk poetry, which can be accessed, for example, through the collection of the Suomen Kansan Vanhat Runot I-XXXIV ([1908-1948] 1997, Gli antichi poemi del popolo finlandese I-XXXIV), in which the majority of the original collected Kalevalian folk poetry has been recorded. Although genres, subgenres and topics in the field of folklore have enjoyed different status, one seems particularly interesting to us e.g. that of spells/incantations. It is not only because of the originality of this genre of ritual poetry, but also because it is apparent how nowadays its tradition is very active and productive in different cultural/artistic fields. Within this framework and with particular attention to the healing spells, we present translations of texts not only dating back to ancient material collected in the 19th century, but also from new sources, ranging from the musical field to the very recent spell against the Corona virus.